Geological formation conditions for lead and zinc ore deposits in the People’s Democratic Republic of Algeria - V. V. Dyakonov; W. Maou; N. А. Pogrebs (Известия высших учебных заведений: Геология и разведка)
Background. New viewpoints on the formation of lead and zinc (Pb and Zn) ore deposits in the People’s Democratic Republic of Algeria are presented.Aim. To develop a geological and structural model for the formation of Pb and Zn ore deposits in Algeria within the paleovolcanic structure.Materials and methods. An analysis of the existing materials on the Pb and Zn deposits of the Algerian Republic was conducted. A structural and genetic scheme for the formation of stratiform Pb and Zn deposits in carbonate rocks was proposed using the example of the sulfate-fumarole activity of Mount Erebus volcano.Results. The stratiform ore deposits of Pb and Zn are of the same age (Oligocene), regardless of the age of the host carbonate rocks.Conclusion. The stratiform deposits of Pb and Zn are the products of a volcanic sulfate-fumarole activity of hydrotherms under the cover of carbonate deposits formed on the slopes of a paleovolcanic structure of the Jurassic-Oligocene age.